Osthole inhibits the progression of human gallbladder cancer cells through JAK/STAT3 signal pathway both in vitro and in vivo. Issue 10 (November 2019) - Le Zou, Tian; Wang, Hong Fei; Ren, Tai; Shao, Zi Yu; Yuan, Rui Yan; Gao, Yuan; Zhang, Yi Jian; Wang, Xu An; Liu, Ying Bin
Abstract : Osthole is an antitumor compound, which effect on Gallbladder cancer (GBC) has been not elucidated. This study focused on its anti-GBC effect and mechanism both in vitro and in vivo . The antiproliferation effect on cell lines NOZ and SGC-996 were measured by cell counting kit-8 (CCK-8) and colony formation assay. The effects on cell apoptosis and cell cycle were investigated by flow cytometry assay. The migration effect was checked by transwell assay and the expressions of proteins were examined by Western Blots. Also, we did an in-vivo experiment by intraperitoneal injection of osthole in nude mice. The results showed that cell proliferation and viability were inhibited in a dose- and time-dependent manner. The similar phenomenon was also found in vivo . Flow cytometric assay confirmed that osthole inhibited cells proliferation via inducing apoptosis and G2/M arrest. Transwell assay indicated that osthole inhibited the migration in a dose-dependent manner. Expression of key proteins related with apoptosis and cell cycle were testified after osthole treatment. Also, we found the key proteins involved in the JAK/STAT3 signal way decreased after osthole treatment. This study suggested that osthole can inhibit the progression of human GBC cell lines, thus maybe a potential drug for GBC treatment.